Perjanjian Internasional yang Dibuat oleh Organisasi Internasional - Suwardi, Sri Setianingsih (Indonesian Journal of International Law, 2007)
Nowadays, International Organizations has been recognized as one of the international law subject after exceeded a long winding road. The logical consequence of the recognition is the capability of International Organization to construct an international agreement as well as a State has done. Nevertheless, there are still several mechanism differences between State and International Organization in construct an international agreement. The main difference is about who has the authority to make a deal in international agreement process. This article explores and analyzes the great effort of international organization to gain the recognition as one of international law subject, also the authority of international organization related to the construction of international agreement.